Ladybug - Llewellyn, Claire; Mendez, Simon (Chanhassen, Minn. : NorthWord Press, 2004)
Describes the physical characteristics and behavior of ladybugs, including their development from egg to adult.
Keywords: Ladybugs -- Development; Ladybugs; Ladybugs